2020
DOI: 10.1002/biot.201900411
|View full text |Cite
|
Sign up to set email alerts
|

Establishing Suspension Cell Cultures for Improved Manufacturing of Oncolytic Adenovirus

Abstract: Recent clinical trials have shown the potential of oncolytic adenoviruses as a cancer immunotherapy. A successful transition of oncolytic adenovirus to clinical applications requires efficient and good manufacturing practice compatible production and purification bioprocesses. Suspension cultures are preferable for virus production as they can reduce process costs and increase product quality and consistency. This work describes the adaptation of the A549 cell line to suspension culture in serum‐reduced medium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…However, it has been shown that it can also be used in the production of adenovirus, , which has become popular again in recent years . A-549, which is also human origin, is a cell line with a very high potential for use after its reliability in viral vaccine production has been demonstrated in more detail. , However, since only approved and commercially used cellular platforms are covered in this review, all these other potential vaccine expression platforms are not elaborated.…”
Section: Animal Cell Culture-based Expression Platforms Used In Vacci...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown that it can also be used in the production of adenovirus, , which has become popular again in recent years . A-549, which is also human origin, is a cell line with a very high potential for use after its reliability in viral vaccine production has been demonstrated in more detail. , However, since only approved and commercially used cellular platforms are covered in this review, all these other potential vaccine expression platforms are not elaborated.…”
Section: Animal Cell Culture-based Expression Platforms Used In Vacci...mentioning
confidence: 99%
“… , This situation creates additional costs in production and prolongs the preprocessing time in preparation for production. Additionally, it is difficult to obtain large amounts of cells because cell proliferation is limited by the available surface area. ,,, Since it is known that primary cultures and diploid cell lines retain their adherent character and have limited adaptability to suspended conditions, they are produced adherently in viral vaccine production, either using microcarriers or in packed-bed bioreactors (such as iCellis) where other suitable support materials are used. , Cells with suspension character have advantages such as ease of scale-up since they are not dependent on any surface, less labor required, growth is limited only by the cell concentration in the nutrient medium, and the cellular microenvironment in the production environment is more homogeneous. , However, as mentioned, since almost all of the expressional platforms used in vaccine production show adherent character, if the use of suspension cultures is aimed in production, the cellular substrates must be adapted to the suspension growth condition. , This adaptation is possible by culturing adherent cells in dynamic systems, using serum-free nutrient media specifically developed for the cell line, or applying both methods simultaneously. ,,, In this way, very high success can be achieved in continuous cell lines. ,, However, since the cellular character changes greatly during adaptation, it must be constantly checked that this suspended culture developed by cell engineering synthesizes the vaccine material in sufficient quantities and in a suitable form for industrial use. Additionally, the safety properties of adapted cells, such as tumorigenicity, should also be re-evaluated and checked. ,, The main disadvantage of suspension cultures is the need for cell-retention devices in case of any nutrient media change or washing process during production …”
Section: Selection Of the Expression Platformmentioning
confidence: 99%
“…Adenovirus harvests from adherent and suspension cell lines differ in multiple aspects, including not only the method of cultivation but also the raw materials used and necessary production equipment. Considering the process scalability, costs, product quality, and its consistency, the choice of upstream platform plays an important role [26]. In terms of robustness, the chromatographic step capacity was checked, and H4 was included as additional material from an adherent cell line.…”
Section: Influence Of Harvest Characteristics On Cim Qa Column Capacitymentioning
confidence: 99%
“…Cell lysis using detergent is easy to perform in the laboratory and at the production scale. In this step, most commonly, non-ionic detergents such as Tween-20 and Tween-80 and ionic detergents such as sodium deoxycholate can be used to solubilize cell membranes and release viruses [ 21 , 22 ]. Tween-20 detergent, also known as Polysorbate-20, is frequently used for protein solubility, protein–lipid, lipid–lipid aggregation, and enveloped virus clearance in the pharma industry [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In downstream processes of adenoviral vectors, incubation times vary from half an hour to 4 h during the release of viruses from the cell [ 22 , 28 ]. The incubation temperature varies between room temperature and 37 °C [ 21 , 22 , 28 ]. However, the effects of incubation periods and temperature on vector yield and stabilization are not well known.…”
Section: Introductionmentioning
confidence: 99%